Проекционно-итерационные модификации метода конечных элементов в краевых задачах теории упругости - Гарт, Э.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
Projective-iterative modifications of the finite-element method to solve the minimum problem in Hilbert spaces are proposed. The effective algorithm for solving the two-dimensional elastic problem of the stress-strain state of an axial loaded plate with rectangular hole, contact problems, and the three-dimensional elastic problem for a multilayer solid is developed.